HFE-Associated Hereditary Haemochromatosis - Emmeke J Eijkelkamp; Thomas R Yapp; Lawrie W Powell (Canadian Journal of Gastroenterology)
Hereditary hemochromatosis is a common inherited disorder of the iron metabolism. Screening studies indicate that it has a prevalence of one in 200 to 400, depending on the population studied, and a carrier rate of about one in seven to one in 10. Feder et al identified the hereditary hemochromatosis gene (HFE) in 1996 and two candidate mutations; the C282Y mutation has been shown to be responsible for the majority of the hereditary hemochromatosis cases worldwide. The gene discovery has led to rapid advances in the field of iron metabolism. Although the basic defect is still not fully understood, much is known about the sequence of events leading to iron overload.